معالجة قناة الجزائرية الثانية للانتخابات الرئاسية بالجزائر 2019م - ياسمين، عقاب (جامعة الوادي university of Eloued, 2020)
Abstract of study : The importance of my studies is evident in an attempt to measure the depth and impartiality of the coverage of the second Algerian channel, for the presidential elections in Algeria for the year 2019 CE, by answering the main question : How did the second Algerian channel track the presidential elections in Algeria in 2019? This study has a heavy scientific weight, given the nature of the prevailing conditions that marred the subject of research on the one hand, and given the value of scientific study in general on the other hand, I mention it as follows: the nature of the prevailing conditions: which gave particularity to the Algerian presidential elections 2019, where it resonated outside the soil of the homeland, And attracted the attention of the lenses of the Arab and Western world together. Internally, the new form of the presidential campaign 2019/2020 AD, with close anticipation from the Algerian people, finally reached the importance of media participation in political events, according to the Code of Ethics for Electoral Practices in Algeria. The value of the scientific study: This research benefits all media outlets by highlighting the importance of diversity, objectivity and credibility that government media must adopt while covering the electoral process while improving treatment methods. It also seeks to enrich the rack of * media treatments for the presidencies of Algeria *. Finally, the importance of content analysis technology as an analysis tool for media contents, despite the continuous and continuous development in other media research tools and techniques. from the core of the main question, fundamental questions emerged, summarized as follows: 1-What are the most prominent topics that the Algerian channel2 focused on during its coverage of the presidential elections in Algeria 2019? And in what artistic style were you presented?2-.What are the sources of the reliable news articles covered in the eighth evening bulletin for the presidency of Algeria 2019?3-. What is the direction of Canal Jerry 2 towards the presidency of Algeria 2019 through the eighth evening bulletin? How were the persuasion methods used?4-Who are the actors who appeared during the coverage of Canal Allegiri 2 for the elections? What are its trends towards the presidency of Algeria 2019.?5-What are the most prominent types of press through which the topics of the eighth evening bulletin were dealt with?6-What is the nature of the elements of the highlights attached to the news article in Canal Allegree 2?7-What kind of media frameworks did Canal Jerry Channel 2 adopt? What are the mechanisms of framing the news bulletin?-8What is the news site in the eighth evening? And how many seconds did the election campaign last? This study relied on the descriptive survey method, while the research community was represented in all eight o'clock news bulletins broadcast on the CANAL ALGERIE2 channel during the presidential elections campaign in Algeria 2019, and legally decided from November 17, 2019 until December 8, 2019 CE, i.e. 22 bulletins I chose 11 leaflets according to the method of random sampling. Using at the same time the technique of observation and content analysis during the process of quantitative and qualitative analysis of samples, as content analysis studies aim to reveal the level of the media message, as it is the primary media product in the communication process, through which the communicator aims to produce the desired effects on the recipient. The results of the analysis process have resulted in the following results: The channel ran the broadcasts of eight o'clock in the evening, according to three mechanisms, highlighting each of the issues of electoral support, national security and stability, then selected from among the news of political participation and popular mobilization, what supports its electoral path, according to subjective, reference frameworks And institutional, while excluding the electoral boycott, with religious and cultural news. The channel intensified its strategic frameworks and the framework specified in the election issue, in an attempt to provide an image of Algerian social harmony and harmony around electoral approval, and the concern for security and stability amid the political chaos in Algeria. The people occupied the largest portion of the newsletter as active personalities that support the electoral process. The candidates granted Abdul MajeedTabun and Ali bin Falis more time on the screen compared to the rest of the candidates. Canal Algerie2 employed methods of mental and emotional persuasion at the expense of intimidation while avoiding the black decade and similar topics.
_دراسة تحليلية لعينة من نشرات الثامنة مساءا _
مذكرة ماستر إعلام واتصال تخصص سمعي بصري
Keywords: الإنتخابات الرئاسية الجزائرية، قناة الجزائرية الثانية; Élections présidentielles algériennes, deuxième chaîne algérienne; Algerian presidential elections, the second Algerian channel